A literary culture in common: the movement of talleres literarios in Cuba 1960s-2000s - Nehru, Meesha (2010)
Emerging organically in the 1960s and soon incorporated into the revolutionary leadership‟s official drive to democratise culture, the Cuban talleres literarios have expanded over the decades into a significant literary movement based on grassroots participation.